A fractional system with five terms: analysis, circuit, chaos control and synchronization. Issue 1 (2nd January 2019) - Wang, Xiong; Kingni, Sifeu Takougang; Volos, Christos; Pham, Viet–Thanh; Vo Hoang, Duy; Jafari, Sajad
ABSTRACT: By introducing fractional derivative, fractional chaotic systems were proposed. A new fractional system with chaos is presented in our work. It is interesting that the system is elegant including only five terms. By using electronic components, we realize the five-term fractional system. Experimental results show chaos of the circuit. Chaos control as well as synchronization of such a five-term fractional system has been investigated.